Difference Between Mordan Soda Ash and Tohor Lime on the Results of the Ivory Cacak Leaf (Sanchezia speciosa) on Wolfis Fabric Using the Pounding Technique - Mutia Mesa Zahra; Adriani Adriani (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
This research is based on the use of ivory cacak leaves (Sanchezia speciosa) to provide motifs and colors using the ecoprint technique. The purpose of this study is to describe the color name and color fastness to washing, the result of ecoprint with a punch/pounding technique using ivory cacak leaves on wolfis material. The type of data in this study is primary data with data collection techniques using research instruments in the form of questionnaires. The color name using mordan soda ash produces the color name of mudy waters brown #AC915C on the tip of the leaf, the name of the color light brown #D7C370 on the leaf bone branch, the name of the color of wheat light brown #E2D4B3 on the mother of the leaf bone, the name of the color camougflage green #777850 on the flesh of the leaf, the name of the color of golden sundance #C1AF68 on the edge of the leaf, and the name of the color of clam shell pink #BDB693 at the base of the leaves. While the color name using the lime mordan produces the name of the golden sundance color #B69F5E on the tip of the leaf, the name of the pale golden color #F2E4AF on the leaf bone branch, the name of the color of wheat light Brown #D8D3B5 on the mother of the leaf bone, the name of the color camougflage green #72794D on the flesh of the leaf, the name of the color golden sundance #BCA76F on the edge of the leaf, and the name of the pale yellow color #E4DDBD at the base of the leaves. The color fading resistance to washing in wolfis materials using mordan soda ash and lime there was a significant difference in the 3rd wash.